The application of sensor networks within mobile cell networks - Mosorov, Volodymyr; Biedron, Sebastian; Panskyi, Taras (Eastern-European Journal of Enterprise Technologies, 2015)
Mobile devices such as mobile phones are getting increasingly popular by the year. Currently, most users cannot imagine doing without these devices that support our daily lives. Using them, however, entails a certain drawback, namely having to conclude an agreement with the mobile network operator, where the user undertakes to operate the device in keeping with the set rules and pay fixed amounts for the communications service provided by the operator. The authors’ overarching idea is both to reduce the costs of using mobile phones and achieves total independence from the mobile operator. To achieve this goal they propose a communications system that omits the mobile network operator’s infrastructure using methods taken from sensor networks. With the technological advancements it is now possible to manufacture devices whose size is in the order of centimetres. This enables the use of sensor nodes on an unprecedented scale and opens new opportunities even for a private user. Initially, sensor networks were wired solutions. The development of wireless and data processing technologies has helped sensor devices to take over a larger area of research. The purpose of this paper is to present the concept proposal of a free and reliable mobile network